Adaptive Media Based on The Game “Maze Marbles” to Improve Concentration in ADHDStudents - Lestari, Virgiana Ajeng; Erlani, Lalan; Bagaskorowati, Riana (Department of Special Education, 2024)
This study aims to produce a product in the form of adaptive media based on the maze marbles game which will be used as a means of increasing student Attention Deficit Hyperactivity Disorder (ADHD). This research method uses the Research and Development method approach or is referred to as an innovative work research method with a research design for the development of maze marbles media using the 4D development model by Thiagarajan. The results of this study indicate that the development of adaptive media based on the maze marbles game has gone through the stages of the development process and product feasibility trials get an overall average value from the recapitulation of experts with an assessment score of 107 with a percentage of 82.30% and included in the very good category. It can be concluded that the development of adaptive media based on the maze marbles game is urgently needed as a means of supporting media and learning media, especially for students with indications of ADHD. However, the validity of increasing the ability of students needs to be carried out in stages and carried out repeatedly so that the expected ability development can be seen.